Studi Pengaruh Pembelajaran Berbasis Proyek Terhadap Kreativitas Siswa Dalam Mata Pelajaran Pendidikan Agama - Ratna Sri Wahyuni; Reviani; Gusmaneli (CV.ITTC INDONESIA, 2024)
This research aims to assess the impact of project-based learning (PBL) on student creativity in religious education subjects. PBL provides opportunities for students to learn actively by completing projects that are appropriate to the subject matter. In religious education, this approach can increase students' understanding of religious values and the ability to apply them in everyday life. This research uses a literature review to analyze the effects of PBL on student creativity and learning outcomes. Research findings show that PBL can improve students' critical thinking, collaboration and problem solving skills. However, there are several challenges in its implementation that require solutions to increase its effectiveness.